Tiny Steps, Giant Leaps: The Place of Micro-Learning in Language and Literature - Ameh Timothy Ojochegbe (Riviera Publishing, 2025)
This study investigates the impact of microlearning on language and literature education at the university level, addressing a significant gap in existing research. The traditional approaches to teaching these subjects often lead to overwhelming experiences for students, hindering retention and engagement. This research explores how microlearning, defined as small, easily digestible learning units, can enhance student retention, creativity, and engagement in real classroom settings. Conducted over six weeks, the study involved 100 undergraduate students and 10 instructors across two English and literature courses. Participants engaged in daily microlearning tasks, such as analyzing poetry, practicing grammar, and experimenting with sentence structures, each designed to be completed within 10–15 minutes. Data collection included focus group discussions, semi-structured interviews, and classroom observations. The findings reveal that microlearning significantly enhances student retention and engagement while fostering creativity in linguistic tasks. However, challenges related to task coherence and content development were identified. This study underscores the transformative potential of microlearning in language and literature curricula, highlighting the need for careful implementation that is aligned with educational objectives. The results provide valuable insights for educators aiming to integrate microlearning effectively into their teaching practices.